TNF-α-308G/A polymorphism contributes to obstructive sleep apnea syndrome risk: evidence based on 10 case-control studies. - Yanping Wu; Chao Cao; Yinfang Wu; Chao Zhang; Chen Zhu; Songmin Ying; Zhihua Chen; Huahao Shen; Wen Li (PLoS ONE)
Objective The aim of our study was to investigate the association between the TNF-α-308G/A polymorphism and obstructive sleep apnea syndrome (OSAS). Method The Medline, Web of Science, EMBASE, Chinese National Knowledge Infrastructure (CNKI), and Cochrane Central Register of Controlled Trials were searched. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to study TNF-α-308G/A polymorphism and risk of OSAS. Result 10 case-control studies were included in our meta-analysis. The results from our study showed that the TNF-α-308G/A polymorphism was significantly associated with risk of OSAS (A vs. G: OR = 1.67, 95% CI = 1.43-1.95). In the subgroup analysis by ethnicity, the statistical similar results were observed both in European (A vs. G: OR = 1.68, 95% CI = 1.35-2.08) and Asian population (A vs. G: OR = 2.02, 95% CI = 1.50-2.71). When stratified by age, a significantly increased risk was observed in adult carries A allele compared with G allele (OR = 1.79, 95% CI = 1.50-2.13), whereas no association was found in children (OR = 1.09, 95% CI = 0.70-1.69). Conclusion Our study suggested that the TNF-α- 308G/A polymorphism contributed to the susceptibility to the risk of OSAS. Additional well-designed large studies are needed to validate our findings.